Analisis Kinerja Keuangan Pemerintah Daerah Kabupaten Gorontalo Tahun 2020-2024 - Sartin Adjira; Rio Monoarfa; Muzdalifah Muzdalifah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the financial performance of the Gorontalo Regency Government during the 2020–2024 period. The research employed a descriptive quantitative method with a non-statistical approach. The data were obtained from local government financial reports and analyzed using effectiveness ratios, efficiency ratios, independence ratios, harmony ratios, growth trend analysis, and predictive analysis. The results indicate that the regional financial performance, as measured by the effectiveness ratio, remains ineffective because the realization of Local Own-Source Revenue (PAD) has not optimally achieved the established targets. The efficiency ratio demonstrates an inefficient condition due to the relatively high expenditure realization compared to revenue realization. The independence ratio falls within the instructive category, indicating a high dependence on transfers from the central government. The harmony ratio reveals that regional expenditures are still dominated by operational spending rather than capital expenditure. Furthermore, growth analysis shows fluctuating trends in regional revenues and expenditures, while predictive analysis suggests positive prospects for future financial performance through the optimization of local revenue sources, expenditure control, and improvements in regional financial management. The findings are expected to serve as an evaluation tool for local governments in enhancing fiscal effectiveness, efficiency, and financial independence in a sustainable manner.